Conceptual model of sustainable lean and green manufacturing management system: Initial stage - Aminuddin, Adam Shariff Adli; Mohd Nawawi, Mohd Kamal (2011)
The concept of lean and green manufacturing management has recently gained interest among the researchers and practitioners in the area of manufacturing management because it can promote good business sense and being environmentally friendly at the same time.The manufacturing process in automotive industry is exceptionally challenging, characterized by increasing complexity and significant relationship with the deterioration of environment.This paper proposes a framework for a sustainable lean and green manufacturing management system with specific emphasize on the automotive industry.The framework consists of a conceptual model which focuses on the initial stages in moving towards planning,design and implementation phases of sustainable lean and green manufacturing management system.